Adjunctive subgingival application of Chlorhexidine gel in nonsurgical periodontal treatment for chronic periodontitis: a systematic review and meta-analysis - Han Zhao; Jingchao Hu; Li Zhao (BMC, 2020)
Abstract Background Subgingival applications of chlorhexidine (CHX) gel are commonly used as an adjunct in nonsurgical periodontal treatment (NSPT) for chronic periodontitis (CP). However, there is lack of systematic review and meta-analysis justifying the effects of adjunctive CHX gel on clinical outcomes. The objective of this meta-analysis was to evaluate the efficacy of adjunctive subgingival administration of CHX gel in NSPT compared to NSPT alone for CP. Methods An electronic search of four databases and a manual search of four journals were conducted up to August 2019. Only randomized controlled trials reporting on the clinical outcomes of subgingival use of CHX gel adjunct to scaling and root planing (SRP), as compared to SRP alone or with placebo, for at least 3 months were included. Primary outcomes were probing pocket depth (PPD) reduction and clinical attachment level (CAL) gain at 3 and 6 months, when data on at least three studies were obtained. Results Seventeen studies were included for qualitative analysis and seven studies for quantitative analysis (four studies for the application of CHX gel adjunct to SRP at selected sites with at least pocket depth ≥ 4 mm and three studies for comparison of full-mouth disinfection (FMD) with subgingival use of CHX gel and full-mouth scaling and root planing (FMSRP). For subgroups, the clinical outcomes between adjunctive use of Xanthan-based CHX gel (XAN-CHX gel) and CHX gel were analyzed. Results indicated a significant improvement of PPD reduction following local adjunctive administration of XAN-CHX gel for SRP at selected sites (MD: 0.15 mm). However, no difference was found in CAL gain. Moreover, no significant difference was observed in PPD and CAL at both 3 and 6 months post-treatment between FMD and FMSRP. Conclusion Adjunctive subgingival administration of XAN-CHX gel at individual selected sites in NSPT appears to provide slight benefits in PPD reduction compared to NSPT alone for CP. Due to the lack of high-quality studies, further studies with larger sample sizes and strict standards are needed to confirm the conclusions.